Engineering Translation Components for Genetic Code Expansion. Issue 8 (30th April 2022) - Kim, Sooin; Yi, Hanbin; Kim, Yurie T.; Lee, Hyun Soo
Graphical abstract: Methods for improving UAA uptake. Highlights: New codon development used for encoding unnatural amino acids (UAAs) Orthogonal tRNA/aaRS pairs in genetic code expansion: essential properties and engineering substrate specificity. Engineering ribosomes and EF-Tu for improved efficiency of UAA incorporation. Biosynthesis of UAAs for autonomous organisms with expanded genetic codes. Methods for improving UAA uptake. Abstract: The expansion of the genetic code consisting of four bases and 20 amino acids into diverse building blocks has been an exciting topic in synthetic biology. Many biochemical components are involved in gene expression; therefore, adding a new component to the genetic code requires engineering many other components that interact with it. Genetic code expansion has advanced significantly for the last two decades with the engineering of several components involved in protein synthesis. These components include tRNA/aminoacyl-tRNA synthetase, new codons, ribosomes, and elongation factor Tu. In addition, biosynthesis and enhanced uptake of non-canonical amino acids have been attempted and have made meaningful progress. This review discusses the efforts to engineer these translation components, to improve the genetic code expansion technology.